Analysis of Factors Influencing on Bio-Gas Production at Fermenting Sewage Sediments - V. A. Sednin; A. V. Sednin; I. N. Prokopenia; A. A. Shimoukovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Problems concerning optimization of a temperature diagram in respect of centralized heat supply systems with steam-turbine thermal power plants having mean initial steam parameters are considered in the paper. The paper shows that up-keeping of optimum temperature of heating water permits to increase efficiency of power-and-heat supply due to additional system economy of fuel.